Da ficcionalização da história: um estudo da metaficção historiográfica em estação das chuvas, de José Eduardo Agualusa - Lima, Danuza Américo Felipe de (2015)
This dissertation aims to analyze the novel Estação das Chuvas, by José Eduardo Agualusa, drawing on the assumptions of postcolonial theory and poetics of postmodernism in converging points of the two reviews. The aim is to demonstrate how the narrative fictionalizes the Angola s conflicting conditions, through historiographical metafiction, discussed by Linda Hutcheon. In this case, recovering the facts during the period pre and post-independence national. Estação das Chuvas is a novel built from the dialogue between fiction and history, therefore, the author turns to the past proposing its reconstruction under a critical bias about the discourses and power positions. In this return, issues are addressed for the Portuguese context of post-colonialism and conflicts of the war surrounding the political independence of Angola. Related to these historical periods, the narrative engenders selfreflection on literature and the prospect about the heterogeneous national identity, multifaceted and creole. In this sense, the reading focuses to analysis the resources used in the novel for the fictionalization of history and for the rethinking of social, cultural and political contexts of Angola.